Software Production and Development Policy Alternatives: Brazil and Singapore - Rauenhorst, Amy M. (Tufts Archival Research Center, 2005)
Volume 13, Issue 1. Winter Accelerated growth in technology, particularly computer technology, has come to play a significant role in shaping national economic policy planning and development. As a part of this growth, the development of an indigenous software industry can provide a critical link between a country's production needs and available computer hardware. Ms. Rauenhorst presents case studies of software development policy in Brazil and Singapore- two regional technology leaders- including the influences of government ideology and foreign investment and the problems of piracy and copyright infringement. She concludes that the divergent paths followed by Brazil and Singapore vividly illustrate options available to developing countries intending to nurture such indigenous industry.